Volvulus caused by a free intraperitoneal staple after laparoscopic appendectomy: A case report. (2019) - Kim, Rachel; Moore, Ryan; Schmidt, Lauren; Martin, Katherine; Sjoholm, Lars Ola; Mason, Leonard; Beard, Jessica
Highlights: Free intraperitoneal staples are usually inert but can have complications. Early obstructive symptoms after appendectomy should warrant prompt work-up. Volvulus can occur due to free staples after laparoscopic appendectomy. Small bowel necrosis due to a free malformed staple required small bowel resection. We recommend removing free staples when seen in order to prevent complications. Abstract: Introduction: Laparoscopic appendectomies are routinely performed using linear staplers. Few case reports have discussed complications from free intraperitoneal staples after appendectomy. We present the first case of a volvulus caused by a free staple that subsequently required bowel resection. Presentation of case: A 27-year-old female underwent laparoscopic appendectomy for uncomplicated appendicitis. The base of the appendix was divided using a laparoscopic gastrointestinal anastomosis (GIA) stapler and the mesoappendix was divided using a LigaSure device. The patient was discharged the following day. Eight days later, the patient returned to the emergency department with severe abdominal pain, emesis, and peritoneal signs. Computed tomography (CT) showed significant pneumoperitoneum and nonspecific small bowel edema. Exploratory laparotomy was performed revealing a necrotic small bowel segment from a malformed, free staple caught on the peritoneum of the small bowel mesentery causing a closed loop obstruction. After reduction and detorsion, the small bowel segment was not viable and required resection. She was discharged on postoperative day four with no additional perioperative complications. Discussion: Mechanical staplers are commonly used in laparoscopic appendectomy and free intraperitoneal staples are generally considered inert. A high index of suspicion should be maintained for the early postoperative appendectomy patient with obstructive symptoms. Conclusion: Inspection of the staple line, choosing the appropriate staple size and cartridge, and removing free malformed staples if seen should be employed during appendectomy to prevent rare but devastating complications.